ASPECTS OF ENVIRONMENTAL LEGISLATION THAT REGULATE THE USE OF WATER IN THE LANDSCAPE OF THE CAMPOS NEUTRAIS OF RIO GRANDE DO SUL (BRAZIL) - Cardoso, Anelize Milano; Madeira, Márlon; Schwanz, Vinícius Bartz; Simon, Adriano Luís Heck (Geosaberes, 2024)
The Campos Neutrais are located in the extreme south of the state of Rio Grande do Sul (Brazil) and are part of the geological context of the Coastal Plain of this state. In the Neutral Fields, landscapes with ecosystems that play a vital role in sustaining life on the Earth's surface predominate. Thus, the objective of this article is to recognize and spatialize the aspects of environmental legislation, in different spheres, that regulate the use of water in the landscape of the Campos Neutrais of Rio Grande do Sul. The methodology used in this work encompassed a thorough research on environmental legislation in different spheres, that is, at the international, national, state and municipal levels, employed in the territory of the Campos Neutrais of Rio Grande do Sul. The results show that recognizing water as a universal heritage promotes a holistic and sustainable approach, encouraging the engagement of public authorities and society in its management and conservation.